Front Cover: Progress in aggregation‐induced emission‐active fluorescent polymeric hydrogels. Issue 3 (29th June 2021) - Lu, Wei; Wei, Shuxin; Shi, Huihui; Le, Xiaoxia; Yin, Guangqiang; Chen, Tao
Abstract : Aggregation‐induced emission (AIE)‐active fluorescent polymeric hydrogels (FPHs) are the marriage of AIE‐active materials and polymeric hydrogels. They are known to bear many advantageous properties such as soft wet nature, tissue‐like mechanical strength, biocompatibility, biomimetic self‐healing feature, facilely tailored structure, as well as responsive fluorescence and volume/shape changes, thus representing a promising category of luminescent materials with many frontiers uses. This Review is intended to give a systematic summary of the recent progress in this young but flourishing research area. (Article number 2021, 2, e37 )